Anchoring Legal Certainty upon the Liability Ambiguities of Autonomous Vessels under International Maritime Law - Fitri Maharani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The emergence of Maritime Autonomous Surface Ships (MASS) technology creates normative ambiguity because the current international legal framework is still human-centric. This research departs from the problematic legal ambiguity regarding MASS in the international maritime law regime and how legal certainty theory views and provides solutions to it. This research aims to analyze the unpreparedness of maritime regulations in reaching the operational reality based on artificial intelligence that separates the locus of control from the physical ship, and formulate the direction of legal reform through the perspective of legal certainty theory. The research method used is normative-doctrinal with a statutory and conceptual approach analyzed qualitatively-deductively. The results of the study indicate the urgency of functional redefinition of the role of the captain and the legal status of the ship, as well as a shift in the paradigm of responsibility from the fault-based liability model to strict liability or product liability due to the risk of systemic failure. This has implications for the demand for restructuring of responsibilities from individual-based to system-based to ensure legal predictability and the effectiveness of flag state control.